Knowledge and attitude of the Jordanian community towards the use of medicinal herbs during COVID-19 pandemic: Females vs males perspective point of view - Malak A. Jaber; Abdul Rahman Al Natour; Mohammad Alnatour; Kenza Mansoor (Trees, Forests and People)
This paper examines the knowledge and attitudes towards complementary and alternative herbal medicine among the Jordanian population by gender during the COVID-19 outbreak. A cross-sectional self-reported survey conducted over two months included 419 participants in Jordan. Data were gathered and analyzed using SPSS V22. The results show that 65.4 % of participants used herbal medicine for COVID-19 symptoms, with higher usage among females (70.7 %) compared to males (51.3 %). For prevention, 44.4 % of participants used herbal medicine, with 78.5 % being females. Commonly used remedies included Anise, Chamomile, Ginger, Mint, Green Tea, and Thyme, with females using them more frequently. The average knowledge level was 72.08 %, with males (77.4 %) scoring higher than females (70.1 %). The knowledge level did not significantly vary across sociodemographic characteristics. Participants aged 19–25 showed less confidence in herbs for prevention, likely due to better health and fewer chronic conditions. A wide range of remedies was cited, and the primary sources of herbs were herbalists and affordable options. Family and friends were the main sources of information, with less reliance on the internet or professionals. The most common preparation methods were boiling or infusion. The study highlights the need for more education from professionals and enhancing the credibility of web-based health information.